Characterization of long-term potentiation of C-fiber-evoked potentials in spinal dorsal horn of adult rat: essential role of NK1 and NK2 receptors - Liu, Xianguo; Sandkühler, Jürgen (Journal of neurophysiology, 1997)
Liu, X.-G. and J. Sandkühler. Characterization of long-term potentiation of C-fiber-evoked potentials in spinal dorsal horn of adult rat: essential role of NK1 and NK2 receptors. J. Neurophysiol. 78: 1973-1982, 1997. Impulses in afferent C fibers, e.g., during peripheral trauma, may induce plastic changes in the spinal dorsal horn that are believed to contribute to some forms of hyperalgesia. The nature of lasting changes in spinal nociception are still not well understood. Here we characterized the long-term potentiation (LTP) of spinal field potentials with a negative focus in superficial spinal dorsal horn evoked by supramaximal electrical stimulation of the sciatic nerve in urethan-anesthetized adult rats. The field potentials studied in this work had high thresholds (≥7 V, 0.5 ms), long latencies (90-130 ms), and long chronaxy (1.1 ms) and were not abolished by muscle relaxation and spinalization. Thus they were evoked by afferent C fibers. In response to 1-Hz stimulation of afferent C fibers, amplitudes of C-fiber-evoked field potentials remained constant, whereas number of action potentials of some dorsal horn neurons increased progressively (wind-up). In all 25 rats tested, high-frequency, high-intensity stimulation (100 Hz, 30-40 V, 0.5 ms, 400 pulses given in 4 trains of 1-s duration at 10-s intervals) always induced LTP (to ∼200% of control), which consistently lasted until the end of recording periods (4-9 h). This tetanic stimulation also significantly decreased mean threshold of C-fiber-evoked field potentials. The C-fiber volley, which was recorded simultaneously in sural nerve, was, however, not affected by the same tetanic stimulation. High-frequency, low-intensity stimulation (100 Hz, 3 V, 0.5 ms) never induced LTP in six rats tested. At an intermediate frequency, high-intensity stimulation (20 Hz, 40 V, 0.5 ms, 400 pulses given in 4 trains of 5 s at 10-s intervals) induced LTP in four out of six rats, which lasted until end of recording periods (3-6 h). In the remaining two rats, no LTP was induced. Low-frequency, high-intensity stimulation (2 Hz, 30-40 V, 0.5 ms, 400 pulses) induced LTP that lasted for 2-8 h in four out of five rats. Intravenous application of neurokinin 1 (NK1) or neurokinin 2 (NK2) receptor antagonist RP 67580 (2 mg/kg, n = 5) or SR 48968 (0.3 mg/kg, n = 5) 30 min before high-frequency, high-intensity stimulation blocked the induction of LTP in all rats tested. In contrast, the same dose of their inactive enantiomers RP 68651 (n = 5) or SR 48965 (n = 5) did not affect the induction of LTP. Spinal superfusion with RP 67580 (1 μM) from 30 min before to 30 min after high-frequency, high-intensity stimulation blocked induction of LTP in all five rats tested. Spinal application of SR 48968 (10 nM) prevented LTP in five out of seven rats. However, when spinal superfusions with RP 67580 (1 μM, n = 3) or SR 48968 (10 nM, n = 3) were started 1 h after high-frequency, high-intensity stimulation, established LTP was not affected. Thus the activation of neurokinin receptors is necessary for the induction but not for the maintenance of LTP of C-fiber-evoked field potentials in spinal dorsal horn. This model may be useful to study plastic changes in spinal cord induced by peripheral C-fiber stimulation. The LTP of C-fiber-evoked field potentials may be a mechanism underlying some forms of hyperalgesia.
Gesehen am 03.05.2021